Neutropenic Enterocolitis: Case report and literature review - Gutierrez Castillo, Aldo (2023)
Typhlitis, is also known as neutropenic enterocolitis, affects the cecum and distal ileum. It was frequently encountered in pediatricpatients who were undergoing treatment for leukemia. Nonetheless, it can affect adult patients, regardless of the cause of the immunosuppression. We report the case of a 20-year-old patient who was receiving chemotherapy for Osteosarcoma, who had a 6-day history of nausea and vomiting, fever sensation, diarrhea, and diffuse abdominal pain. Physical examination was relevant for hemodynamic instability, a distended and tender abdomen predominantly in the right iliac fossa. The laboratory workup showed severe neutropenia, thrombocytopenia, and electrolyte disturbances. The image studies evidenced edema of the ascending colon and cecum. Treatment was started with vasopressor support, correction of electrolyte alterations, blood cell and platelet transfusion, G-CSF, hydration, broad spectrum antibiotic therapy, initially with adequate clinical and laboratory response. After a few days, he presented lower gastrointestinal bleeding which was treated by conservative management. In conclusion, typhlitis must be suspected in every patient developing neutropenia as a reaction to chemotherapy and who also presents gastrointestinal symptoms, such as nausea, vomiting, diarrhea, and intense abdominal pain.